Pengembangan Lembar Kerja Peserta Didik Berbasis Pendekatan Inkuiri Terbimbing melalui Materi Pewarisan Sifat pada Makhluk Hidup Kelas IX SMP/MTs - Anggraeny, Widya; Risdawati, Renny; Maizeli, Annika (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The background to the development of guided inquiry-based LKPD is the incompatibility of the LKPD used with the proper LKPD criteria. This study aims to determine the feasibility of guided inquiry-based worksheets seen from the aspects of feasibility of content, language, didactics, and graphics by validators/educators, and to know the practicality of guided inquiry-based worksheets by educators and students. This research is a development research using a modelFour-D (4-D) The research instruments used were: (1) LKPD validity test questionnaire by validators and study field teachers, (2) practicality test questionnaire by educators and students. The results of the LKPD validation research by lecturers and educators obtained a percentage of 91.8% with very valid criteria. The practicality test results by educators obtained a percentage of 84.3% with very practical criteria. Student Worksheet Practicality Test Results obtained a percentage of 86.1% with very practical criteria.